Characterization and Conversion of Sludge Palm Oil (SPO) into Biodiesel - Sim, Siong Fong; Lau, Seng; Benedict, Samling; Nur Syahidda Ani, Moksin; Nursyafira Adzira, Halmi; Amelia Laccy, Jeffrey Kimura; Clarence, Chin; William, Liang (MJChem, 2022)
Sludge Palm Oil (SPO) is a potential low-cost feedstock for biodiesel production. The conversion efficiency and the quality of biodiesel produced is governed by the feedstock and the conversion reaction. To our knowledge, the potential of SPO produced by palm oil mills in Sarawak has yet to be explored. Hence, this paper aims to characterize the SPO obtained from Sarawak palm oil mills and to optimize the predominant conversion reaction. The SPO was converted into biodiesel via a sulphuric acid catalyzed esterification reaction, followed by transesterification using potassium hydroxide and methanol. This SPO contained 1.30 - 10.15% moisture, 2.91 - 7.63% sediment and 47.05 – 87.86% free fatty acids (FFA). The optimum esterification conditions identified were: SPO:methanol ratio (1:10), sulphuric acid concentration (1.84%) and reaction time (3.25 hr). Under these conditions, the biodiesel yield was 74% with an FFA conversion efficiency of 79.87%. The water produced during the esterification process was found to hinder the reaction, reducing both conversion efficiency and biodiesel yield. The findings of this study offer important insights about the challenges and feasibility of biodiesel conversion from SPO, where esterification is inevitable due to its high FFA content.